2003
DOI: 10.1093/jb/mvg005
|View full text |Cite
|
Sign up to set email alerts
|

Development and Characterization of a Novel Fusion Protein Composed of a Human IgG1 Heavy Chain Constant Region and a Single-Chain Fragment Variable Antibody against Venezuelan Equine Encephalitis Virus

Abstract: Murine monoclonal antibody 1A4A1 has been shown to recognize a conserved neutralizing epitope of envelope glycoprotein E2 of Venezuelan equine encephalitis virus. It is a potential candidate for development of a second generation antibody for both immunodiagnosis and immunotherapy. In order to minimize the immunogenicity of murine antibodies and to confer human immune effector functions on murine antibodies, a recombinant gene fusion was constructed. It encoded a human IgG1 heavy chain constant region and a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The synthetic APA antibody was directed against P. aeruginosa (strain O6) and consists of a single‐chain variable fragment (Hemachandra et al. , 2001) fused to the human IgG1 heavy chain constant region (CH1–CH3), which adds effector functions to the antibody (Hu et al. , 2003).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The synthetic APA antibody was directed against P. aeruginosa (strain O6) and consists of a single‐chain variable fragment (Hemachandra et al. , 2001) fused to the human IgG1 heavy chain constant region (CH1–CH3), which adds effector functions to the antibody (Hu et al. , 2003).…”
Section: Methodsmentioning
confidence: 99%
“…The construct used to express human IL-10 in plants (IL10-ELP) contains a translational fusion with an elastin-like polypeptide (ELP) tag and was described in detail by Conley et al (2009a). The synthetic APA antibody was directed against P. aeruginosa (strain O6) and consists of a single-chain variable fragment (Hemachandra et al, 2001) fused to the human IgG1 heavy chain constant region (CH1-CH3), which adds effector functions to the antibody (Hu et al, 2003). A (His) 6 tag was included for detection of the APA protein.…”
Section: Plant Expression Vectorsmentioning
confidence: 99%
“…An scFv‐Fc is a single‐gene product, which can dimerize through hinge region cysteine residues, thus providing the avidity effect. Several systems have been developed for the expression of such antibody‐like molecules 35–37 . Such fusion molecules have a prolonged serum half‐life in vivo 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Such glycosylation is considered to be important for induction of effector functions 42 . The scFv‐Fc fusion molecules bind to C1q 37 and can trigger superoxide production through FcγRI 41 . It has been observed that scFv‐Fc fusion proteins can activate complement cascade and induce antibody‐dependent cell‐mediated cytotoxicity 43,44 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation